Individual modeling of the competition activities for elite female ski races during the 2006-2007 - Cepulenas, A. (Science and Skiing IV, 2008)
INTRODUCTION: Individual planning of the competition activities for elite skiers racers (women) during a micro cycle is a very important optimization factor for the sportive training [Rusko, 2003]. The goal of this research is to analyze the individual competition participation Systems of the Champions and winners of the individual racing during the World Ski Championship in Sapporo 2007.